Nanoliquid Jet Impingement Heat Transfer for a Phase Change Material Embedded Radial Heating System - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Asme, 2022)
Nanoliquid impingement heat transfer with a phase change material (PCM) installed radial system is considered. The study is performed by using the finite element method for various values of Reynolds numbers (100 <= Re <= 300), height of PCM (0.25H <= h(pcm) <= 0.75H), and plate spacing (0.15H <= h(s) <= 0.40H). Different configurations using water, nanoliquid, and nanoliquid + PCM are compared in terms of heat transfer improvement. Thermal performance is improved by using PCM, while best performance is achieved with nanoliquid and PCM-installed configuration. At Re = 100 and Re = 300, heat transfer improvements of 26% and 25.5% are achieved with the nanoliquid+ PCM system as compared to water without PCM. The height of the PCM layer also influences the heat transfer dynamic behavior, while there is 12.6% variation in the spatial average heat transfer of the target surface with the lowest and highest PCM heights while discharging time increases by about 76.5%. As the spacing between the plates decreases, average heat transfer rises and there is 38% variation.
Keywords: jet impingement; phase change material; nanoliquid; finite element method